The hypercoagulable state in hyperthyroidism is mediated via the thyroid hormone β receptor pathway. Issue 6 (June 2016) - Elbers, Laura P B; Moran, Carla; Gerdes, Victor E A; van Zaane, Bregje; Meijers, Joost C M; Endert, Erik; Lyons, Greta; Chatterjee, Krishna; Bisschop, Peter H; Fliers, Eric
Abstract : Objective: Hyperthyroidism is associated with a hypercoagulable state, but the underlying mechanism is unknown. Patients with resistance to thyroid hormone (RTH) due to defective thyroid hormone receptor β (THRB or THRB ) exhibit elevated circulating thyroid hormones (TH) with refractoriness to TH action in THRB -expressing tissues. We tested the hypothesis that the hypercoagulable state in hyperthyroidism is mediated via the THRB . Design: We conducted a cross-sectional study from November 2013 to January 2015 in 3 hospitals in the Netherlands and the United Kingdom. Methods: Patients with RTH due to defective THRB ( n= 18), patients with hyperthyroidism ( n= 16) and euthyroid subjects ( n= 18) were included. TH concentrations and markers of coagulation and fibrinolysis were measured. Data are expressed as median (interquartile range). Results: Free thyroxine (FT4 ) levels were slightly higher in hyperthyroid patients than in RTH patients (53.9 (30.5–70.0) and 34.9 (28.4–42.2)pmol/L, respectively, P =0.042). Both groups had raised FT4 levels compared with euthyroid subjects (14.0 (13.0–15.8)pmol/L, P ≤0.001). Levels of von Willebrand factor (VWF), factor (F) VIII, fibrinogen andd -dimer were significantly higher in hyperthyroid patients than in RTH patients (VWF 231 (195–296) vs 111 (82–140)%, FVIII 215 (192–228) vs 145 (97–158)%, fibrinogen 3.6 (3.0–4.4) vs 2.8 (2.5–3.2)g/L, d -dimer 0.41 (0.31–0.88) vs 0.20 (0.17–0.26)mg/L, respectively, P ≤0.001), while there were no differences between RTH patients and euthyroid controls. Conclusions: Parameters of coagulation and fibrinolysis were elevated in hyperthyroid patients compared with patients with RTH due to defective THRB, whereas these parameters were not different between euthyroid controls and RTH patients, despite elevated FT4 concentrations in RTH patients. This indicates that the procoagulant effects observed in hyperthyroidism are mediated via the THRB .